Pengaruh Penambahan Pati Ubi Kayu pada Bahan Cetak Alginat Terhadap Stabilitas Dimenisi Model Gigi Tiruan - M Zulkarnain; Jaasphreet Kaur Harchan Singh (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Alginate is one of the most widely used dental impression material used by dentists. When the process of syneresis and imbibitions occurs, it resulted in changes of dimensional stability of alginate and to prevent the occurrence changes in dimensional stability modification of impression material is done by adding cassava starch. The purpose of this study was to determine the effect of cassava starch in various concentrations of 40%, 50%, 60% into impression material of alginate with pouring of type III gypsum after 5, 10 and 15 minutes towards dimensional stability of denture model. This was a laboratory experimental study using a copper splint–metal (12,5 mm inside diameter). The total of 60 samples are classified to 12 groups. Samples were measured using digital calliper then analyzed by One-Way Anova test followed by LSD test. Based on One-Way Anova, the results shows significant result in addition of cassava starch concentration 40%, 50%, 60% into alginate with pouring of type III gypsum after 5 minutes (B1, A1.1, A2.1 dan A3.1) with p = 0,043 (p<0,05), after 10 minutes (B2, A1.2, A2.2 dan A3.2) with p = 0,005 (p<0,05) and after 15 minutes (B3, A1.3, A2.3 dan A3.3) with p = 0,003 (p<0,05). The result of LSD test showed a significant difference in all the groups with (p<0,05). The results showed the addition of cassava starch in various concentrations have influence on the dimensional stability of alginate impression material. The addition of 40% cassava starch into impression material of alginate has the best stability than other concentration.